State, market or community failure? Untangling the determinants of groundwater depletion in Copiapó (Chile). Issue 2 (4th March 2019) - Rinaudo, Jean-Daniel; Donoso, Guillermo
Abstract: This article analyzes the factors that explain why groundwater can be over-exploited despite the existence of sophisticated water laws, institutions and effective state agencies responsible for water management. The analysis is based on a case study conducted in the Copiapó Valley in northern Chile. Based on an analysis of water use data, policy documents and interviews with a variety of stakeholders, the article highlights the state's failure to perform some of its key missions and the ineffectiveness of groundwater users' associations in water management despite a very supportive legal framework. The article concludes with some recommendations on how ensure long-term sustainable groundwater use.